Biodiversity and Ecology of Some Macro zoobenthos (Hirudinea, Gastropod) of Shiraganbulak Spring, Fergana Valley, Uzbekistan (Texas Journal of Agriculture and Biological Sciences, 2023)
The number of springs in the Ferghana Valley is very large and diverse. For this reason, the biological diversity of macrozobenthos organisms is high among them. This article describes the species composition of leeches and fresh-water gastropods living in the Shiraganbulak spring located in the southeastern part of the Fergana Valley, as well as their ecological description. Researches were carried out in generally accepted zoological and ecological methods. According to the research results, it was found that 2 species of leeches and 5 species of fresh-water gastropods live in Shiraganbulak spring